Pengasuhan dan Pendidikan Anak dalam Islam - Mikyal Oktarina (2021)
Parenting and education of children in Islam is an important pillar of the main task for every parent. Because this is our opportunity as parents, our golden opportunity to provide care and education to shape children's character. We know that we feel together, the Indonesian nation is currently starting to deplete the morals of every child and young generation. So that nurturing and education in Islam can be one solution. Nurturing, educating, fostering, familiarizing, and guiding children optimally based on the Qur'an and the Sunnah of the Prophet Muhammad. Children are in the golden age and the success of parenting at this golden age is a determinant of the success of children in their teens and adults so that later they will produce children who have noble character and are able to become a golden generation by bringing the light of glory to this nation.